2017
DOI: 10.1038/s41467-017-02148-1
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic asymmetric synthesis of a nitrogen heterocycle through stereocontrolled direct photoreaction from electronically excited state

Abstract: The reactivity of photoexcited molecules has been extensively studied for decades but until today direct bond-forming reactions of such excited states in a catalytic and asymmetric fashion are restricted to the synthesis of cyclobutanes via [2 + 2] photocycloadditions. Herein, we demonstrate a previously elusive visible-light-induced catalytic asymmetric [2 + 3] photocycloaddition of alkenes with vinyl azides. A wide range of complex 1-pyrrolines are obtained as single diastereoisomers and with up to >99% enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 36 publications
(32 reference statements)
1
47
0
2
Order By: Relevance
“…Meanwhile, energy transfer (EnT) processes have drawn attention as an alternative visible-light photocatalysis in an increasing number of transformations [27][28][29] . For example, synthesis of N-heterocycles via sensitization of azido compounds [30][31][32][33][34][35] and isomerization of alkenes [36][37][38] have been described. Also, alkene-alkene [2 + 2] cycloaddition for the synthesis of cyclobutanes in inter-and intramolecular fashion based on the EnT process has been reported [39][40][41][42][43][44][45][46] .…”
mentioning
confidence: 99%
“…Meanwhile, energy transfer (EnT) processes have drawn attention as an alternative visible-light photocatalysis in an increasing number of transformations [27][28][29] . For example, synthesis of N-heterocycles via sensitization of azido compounds [30][31][32][33][34][35] and isomerization of alkenes [36][37][38] have been described. Also, alkene-alkene [2 + 2] cycloaddition for the synthesis of cyclobutanes in inter-and intramolecular fashion based on the EnT process has been reported [39][40][41][42][43][44][45][46] .…”
mentioning
confidence: 99%
“…When using N ‐acylpyrazole 2 b as substrate, the C−C formation product 3 b was formed with inferior yield (54 %) and decreased ee (90 %; entry 3). However, we found that a 3‐Me‐substituted pyrazole ( 2 c ) instead of a 3,5‐di‐Me‐substituted pyrazole moiety ( 2 b ) not only improved the yield (84 %) but also afforded higher enantioselectivity (95 % ee ; entry 4) . A β‐disubstituted β‐methyl‐β‐phenyl alkene ( 2 d ) did not provide any desired product under these optimized conditions (entry 5).…”
Section: Figurementioning
confidence: 97%
“…37 Here, the authors proposed that following addition to the double bond and subsequent dinitrogen extrusion, a 1,5‐diradical is initially formed. The 1‐pyrroline products 28 were obtained with high levels of enantioselectivity.…”
Section: Activation By Lewis Acidsmentioning
confidence: 99%